If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 7)(x + -8) = 8 Reorder the terms: (7 + 4x)(x + -8) = 8 Reorder the terms: (7 + 4x)(-8 + x) = 8 Multiply (7 + 4x) * (-8 + x) (7(-8 + x) + 4x * (-8 + x)) = 8 ((-8 * 7 + x * 7) + 4x * (-8 + x)) = 8 ((-56 + 7x) + 4x * (-8 + x)) = 8 (-56 + 7x + (-8 * 4x + x * 4x)) = 8 (-56 + 7x + (-32x + 4x2)) = 8 Combine like terms: 7x + -32x = -25x (-56 + -25x + 4x2) = 8 Solving -56 + -25x + 4x2 = 8 Solving for variable 'x'. Reorder the terms: -56 + -8 + -25x + 4x2 = 8 + -8 Combine like terms: -56 + -8 = -64 -64 + -25x + 4x2 = 8 + -8 Combine like terms: 8 + -8 = 0 -64 + -25x + 4x2 = 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. -16 + -6.25x + x2 = 0 Move the constant term to the right: Add '16' to each side of the equation. -16 + -6.25x + 16 + x2 = 0 + 16 Reorder the terms: -16 + 16 + -6.25x + x2 = 0 + 16 Combine like terms: -16 + 16 = 0 0 + -6.25x + x2 = 0 + 16 -6.25x + x2 = 0 + 16 Combine like terms: 0 + 16 = 16 -6.25x + x2 = 16 The x term is -6.25x. Take half its coefficient (-3.125). Square it (9.765625) and add it to both sides. Add '9.765625' to each side of the equation. -6.25x + 9.765625 + x2 = 16 + 9.765625 Reorder the terms: 9.765625 + -6.25x + x2 = 16 + 9.765625 Combine like terms: 16 + 9.765625 = 25.765625 9.765625 + -6.25x + x2 = 25.765625 Factor a perfect square on the left side: (x + -3.125)(x + -3.125) = 25.765625 Calculate the square root of the right side: 5.075985126 Break this problem into two subproblems by setting (x + -3.125) equal to 5.075985126 and -5.075985126.Subproblem 1
x + -3.125 = 5.075985126 Simplifying x + -3.125 = 5.075985126 Reorder the terms: -3.125 + x = 5.075985126 Solving -3.125 + x = 5.075985126 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.125' to each side of the equation. -3.125 + 3.125 + x = 5.075985126 + 3.125 Combine like terms: -3.125 + 3.125 = 0.000 0.000 + x = 5.075985126 + 3.125 x = 5.075985126 + 3.125 Combine like terms: 5.075985126 + 3.125 = 8.200985126 x = 8.200985126 Simplifying x = 8.200985126Subproblem 2
x + -3.125 = -5.075985126 Simplifying x + -3.125 = -5.075985126 Reorder the terms: -3.125 + x = -5.075985126 Solving -3.125 + x = -5.075985126 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.125' to each side of the equation. -3.125 + 3.125 + x = -5.075985126 + 3.125 Combine like terms: -3.125 + 3.125 = 0.000 0.000 + x = -5.075985126 + 3.125 x = -5.075985126 + 3.125 Combine like terms: -5.075985126 + 3.125 = -1.950985126 x = -1.950985126 Simplifying x = -1.950985126Solution
The solution to the problem is based on the solutions from the subproblems. x = {8.200985126, -1.950985126}
| 6(2x-1)=5(x+3) | | (x+6)(x-6)(2x-5)=0 | | 5(a+4)=4(a-3) | | 5(2x+3)=25 | | 4X-40=12+6X-6X | | -3(p-4)=21 | | 3(2t+1)=21 | | 5(m-4)=35 | | 2(4x-3)=30 | | (1/4)x-1=7 | | 9x-2=4(x+3) | | 2x+y+3yi=5-xi | | 3x^2-21x+21=x^2-4x | | y=4*10 | | 0.20x+0.5(4-x)=.10(5) | | 120=90 | | 9(105)+3(104)+5(103)+3(102)+7(101)=1 | | -133+5x=101+14x | | -3(y+1)=15 | | -2(3x-1)=20 | | 6(x-2)=28 | | 27x+x=135 | | 2(5x-1)=28 | | -29-2x=-4x+51 | | 8(2x-1)=64 | | t=2g+2v | | 7(m-4)=14 | | 3(y+1)=15 | | 6(3m-2)=2(2m+1) | | 4y=7y-27 | | -249-6x=-17x+70 | | 10x-2=14+2x |